Hubungan Pemberian Asi Eksklusif dan Bayi Berat Lahir Rendah (BBLR) dengan Kejadian Pneumonia pada Balita di Wilayah Puskesmas Kamonji - Linda Linda (Poltekkes Kemenkes Palu, 2018)
Pneumonia is the premiere killer of toddlers in the world and in Indonesia. In Indonesia pneumonia is the cause of 15% of infant mortality is estimated as many as 922,000 under-fives in 2015. Puskesmas Kamonji is a health center that has the highest number of pneumonia cases in the city of Palu is 422 cases in 2015. Based on evidence that the risk factor of pneumonia is the lack of breastfeeding exclusive, malnutrition, indoor air pollution, low birth weight (LBW), population density, and lack of measles immunization. The purpose of this study is known factors associated with the incidence of pneumonia, namely Exclusive breastfeeding and history of low birth weight (LBW). The type of research used is analytical survey with case control approach. The samples in this study were all mothers who had children under 12-59 months in the Kamonji Puskemas Working Area consisted of 70 samples consisting of 35 case samples and 35 control samples. This research uses Chi-square statistical analysis with 5% error rate (α = 0,05) and trust level 95%. The results showed that exclusive breastfeeding (P value = 0.147) and low birth weight (P Value = 1,000) did not correlate with pneumonia occurrence in children aged 12-59 months. The conclusion in this study was no association between exclusive breastfeeding and the incidence of pneumonia and no association between low birth weight infants and the incidence of pneumonia. Suggestions for Health Officers to continue to give counseling about the importance of healthy living behavior teaches the community how important to wash hands with soap and keep the nutritional status of toddlers is always good.